Replication of white etching area evolution using novel modified dynamic load pin-on-disc tribometer on bearing steel. (October 2018) - Sreeraj, K.; Ramkumar, P.
Abstract: A novel modified dynamic load Pin-on-disc tribometer design along with the real time hydrogenating lubrication methodology is experimented to replicate "white etching area" (WEA) formation on bearing steel in laboratory level testing. Controlled formation of white etching area within a short duration has been achieved with the help of this new approach. Investigation of subsurface microstructural changes has opened a new insight in analysing the sequential formation of white etching area associated with premature rolling element bearings failure. The dynamic loading under hydrogenation establishes the sequential microstructural changes such as clustering, agglutination and deformation followed by dissolution of cementites to form WEA in the bearing steel. Graphical abstract: Highlights: A novel dynamic load PoD tribometer with newly formulated hydrogenating lubricant used to replicate white etching area. New methodology achieved the WEA replication within 2.15 × 10 5 cycles, which is 1/10th of contact cycles reported earlier. The WEA inception sequence as clustering, agglutination, cementite deformation and dissolution into matrix is established. The incremental increase of hardness coupled with micro-structural changes in bearing steel is measured and established.